2012
DOI: 10.1002/ejoc.201201082
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized N‐Heterocyclic Carbene Ligands for Dual Enantioselective Control in the Cu‐Catalyzed Conjugate Addition of Dialkylzinc Compounds to Acyclic Enones

Abstract: A series of highly tunable, functionalized azolium compounds have been synthesized from chiral α‐amino acid derivatives such as β‐amino alcohols or α‐amino esters. The combination of a Cu salt and a chiral azolium efficiently facilitated the asymmetric conjugate addition (ACA) reactions of acyclic enones with dialkylzinc under ambient conditions without temperature control. Of the (hydroxy amide)‐functionalized azolium ligand precursors, which were derived from β‐amino alcohols, an azolium salt containing a te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Sakaguchi and co-workers [ 65 ] further extended this work and synthesized a series of highly tunable functionalized NHC-precursor azolium salts. The efficacy of the combination of these salts with Cu salts as catalyst was investigated for the asymmetric conjugate addition (ACA) of dialkylzinc to acyclic enones and it was found that the use of an azolium salt with a sterically bulky alkyl substituent such as N -CHRR (e.g., NCHPh 2 in 123 ) on the azolium ring results in a marked increase in the enantioselectivity of the ACA reaction.…”
Section: Reviewmentioning
confidence: 99%
“…Sakaguchi and co-workers [ 65 ] further extended this work and synthesized a series of highly tunable functionalized NHC-precursor azolium salts. The efficacy of the combination of these salts with Cu salts as catalyst was investigated for the asymmetric conjugate addition (ACA) of dialkylzinc to acyclic enones and it was found that the use of an azolium salt with a sterically bulky alkyl substituent such as N -CHRR (e.g., NCHPh 2 in 123 ) on the azolium ring results in a marked increase in the enantioselectivity of the ACA reaction.…”
Section: Reviewmentioning
confidence: 99%
“…In contrast to the conjugate addition reactions of organometallic compounds with cyclic enones, few highly enantioselective reactions of acyclic enones have been reported [71,[82][83][84][85][86][87][88][89][90][91][92][93]. We then focused on studying the Cu-catalyzed asymmetric 1,4-addition reaction of acyclic enone with Et 2 Zn using this promising class of bis(NHC) chiral ligand L1.…”
Section: Catalytic Asymmetric Conjugate Addition Reaction Of Acyclic mentioning
confidence: 99%
“…For example, 3 was reacted with Et 2 Zn catalyzed by Cu(OTf) 2 /L4 to afford (S)-4, whereas (R)-4 was obtained in the same reaction with the Cu(acac) 2 /L4 catalytic system [74]. However, no reversal of enantioselectivity was observed in the Cu-catalyzed 1,4-addition reaction of acyclic enone when changing the Cu precatalyst in the presence of L4 [71]. Therefore, to the best of our knowledge, this is the first example of switchable enantioselectivity in a catalytic conjugate addition reaction of acyclic enone, with the same chiral ligand.…”
Section: Catalytic Asymmetric Conjugate Addition Reaction Of Acyclic mentioning
confidence: 99%
See 1 more Smart Citation
“…of 98.5:1.5. Alternatively, benzimidazolium‐based ligands such as 36 and 37 can assist conjugate additions to linear enones, albeit with slightly lower enantioselectivity . Owing to the fact that the benzimidazole backbone bears two alkyl substituents on the nitrogen atoms, these ligands can be prepared from amino acids in three steps.…”
Section: Application In Catalysismentioning
confidence: 99%